Synthesis of ZnO nanoparticles by a hybrid electrochemical-thermal method: influence of calcination temperature (Bangladesh Journal of Scientific and Industrial Research, 2015)
ZnO nanoparticles (NPs) with size less than 100 nm were successfully prepared by a hybrid electrochemical-thermal method using metallic zinc and NaHCO3 without the use of any zinc salt, template or surfactant. The NPs were characterized by Fourier transform infra-red (FT-IR) spectroscopy, UV-visible spectroscopy, photoluminescence spectroscopy (PL), thermo-gravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy. UV-visible spectral analysis indicated that the particle size increased with increasing calcination temperature. The band gap (3.91-3.83 eV) was higher for synthesized ZnO NPs than their bulk counterparts (3.37 eV). The FT-IR spectra at different calcination temperatures showed the characteristic band for ZnO at 450 cm-1 to be prominent with increasing temperature due to the conversion of precursor into ZnO. The wurtzite hexagonal phase was confirmed by XRD analyses for ZnO NPs calcined at 700oC. The green photoluminescent emission from ZnO NPs at different calcination temperatures is considered to be originated from the oxygen vacancy or interstitial related defects in ZnO. SEM images clearly showed that the NPs are granular and of almost uniform size when calcined at higher temperatures. EDX spectra further confirmed the elemental composition and purity of ZnO obtained on calcination at 700oC. The NPs are well dispersed near or above calcination temperature of 700oC.Bangladesh J. Sci. Ind. Res. 50(1), 21-28, 2015